Panentheism and New Materialism. Issue 2 (1st April 2022) - Reader, John
Abstract : 'New materialism' develops the notion that all life, not just human life, is dynamic and vital: matter is always more than itself. The implications of this are not only political and philosophical, but also theological, in terms of how God is understood. This article, drawing on the work of Catherine Keller, suggests that contemporary theology should incorporate – as panentheism does – a sense of both proximity and magnitude, the relational and the ineffable, God's entanglement with the processes of creation and yet God's distinction from them. It argues that new materialism, strong on the relational aspect, needs to be complemented by the emphasis on distinction which the balance of panentheism maintains.